Redox regulation of mitochondrial dynamics and function in parkinson’s disease - Santos, Fabiana Alexandra Carvalho dos (2023)
Tese de mestrado, Ciências Biofarmacêuticas, 2023, Universidade de Lisboa, Faculdade de Farmácia.